Shape Coexistence in Odd-Z Isotopes from Fluorine to Potassium - Myeong-Hwan Mun; Panagiota Papakonstantinou; Youngman Kim (Particles)
The shape of a nucleus is one of its fundamental properties. We conduct a systematic investigation of shape coexistence in odd-Z nuclei from fluorine to potassium using the deformed relativistic Hartree–Bogoliubov theory in continuum. First, we present a simple argument regarding the energy differences between degenerate vacua, which can serve as a criterion for identifying candidates for shape coexistence. We then predict isotopes that exhibit shape coexistence.